Mutual binary solubilities: perfluoromethylcyclohexane-hydrocarbons - Bernardo-Gil, M. G. (1988)
Mutual binary solubility data for perfluoromethylcyclohexane+n-hexane, n-heptane, n-octane, n-nonane, 1-hexene and 1-heptene are reported. NRTL and UNIQUAC parameters, for each experimental temperature, were obtained using a NewtonRaphson technique and the parameters so obtained were linearly correlated with T and T1. UNIFAC group parameters for the interaction CH2/CF3 and CH=CH2/CF3 were obtained from mutual solubility data using the same technique. UNIFAC parameters were correlated with the number of carbon atoms and temperature.